Acremonium arthrinii sp. nov., a mycopathogenic fungus on Arthrinium yunnanum - Yang, Chun-Lin; Xu, Xiu-Lan; Jeewon, Rajesh; Boonmee, Saranyaphat; Liu, Ying-Gao; Hyde, Kevin D. (Phytotaxa, 2019)
Acremonium arthrinii sp. nov. was collected from Phyllostachys heteroclada in the forest of Sichuan Province, China. This mycopathogenic fungus was frequently found on the top of the ascomata of Arthrinium yunnanum, and presumably causes its death. In this study, the new species was examined morphologically and maximum likelihood and Bayesian analyses of a combined LSU, SSU, ITS and TEF 1-α were performed to clarify the taxonomic affinity of the species. Acremonium arthrinii can be distinguished from other Acremonium species based on conidiogenesis, size differences in conidiophores, conidiogenous cells and conidia, and its DNA sequence differences and phylogeny. Detailed descriptions, micrographs and phylogenetic relationships of the new taxon were provided.